Impact of Customer Experience on Customer Loyalty, With A Particular Focus on The Role of Customer Satisfaction - Supriyanto, Supriyanto; Nathanael, Austin; Rozi, Fakhrur (Universitas Indonesia Mandiri, 2025)
The internet is one of the impacts of modern technological development that has the capacity to transform the manner in which marketing communication is conducted from face-to-face (conventional) to screen-to-face (digital marketing). The objective of this research is to examine the customer base of Caribbe Caffe. The data collection method employed in this study utilizes the communication method. Therefore, an online questionnaire was disseminated via Google Forms to a sample of 100 respondents who had previously used or purchased products at Caribbe Cafe. The procedure employed for model testing and data processing utilizes a structural equation model with SmartPLS 3.0 and SPSS 25. The resulting output indicates that customer experience exerts a positive and significant influence on customer satisfaction. Furthermore, customer experience demonstrates a positive and insignificant effect on customer loyalty. Additionally, customer satisfaction exhibits a positive and significant effect on customer loyalty. Finally, customer experience displays a positive and significant effect on customer loyalty, albeit indirectly through customer satisfaction. The findings of this study indicate that three of the four hypotheses are substantiated by substantial positive evidence, namely, customer experience and its impact on customer satisfaction, customer experience and its impact on customer loyalty, and customer experience and its impact on customer loyalty through customer satisfaction. However, the fourth hypothesis, which pertains to the direct relationship between customer experience and customer loyalty, is rejected, and the results of the analysis are inconsequential.